2013
DOI: 10.3724/sp.j.1005.2013.00703
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and potential utilization of maize populations in America region

Abstract: Introgression of exotic maize (Zea mays L.) germplasm is an effective approach to broadening the genetic base of Chinese germplasm. America is the center of maize origin and germplasm diversity. By analyzing general combining ability effects and heterosis responses among maize populations from the U.S., International Maize and Wheat Improvement Center (CIMMYT), and Brazil studied by different authors, 24 elite maize populations from America region, including eight U.S. populations, eight CIMMYT populations, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…North American germplasm plays an important role in China's corn yield potential, and their genetic contribution to Chinese corn has been increasing [5][6]. Using American maize germplasm is an effective way to improve the diversity of Chinese maize germplasm for identified and screened favorable allele donors due to its clear genealogical origin and abundant genetic variation [7]. Previous studies have shown that the growth period, the silking stage, the ear height, the plant height, and the kernel moisture concentration at the R6 stage could be used to determine a maize germplasm suitable for mechanical harvesting [8].…”
Section: Introductionmentioning
confidence: 99%
“…North American germplasm plays an important role in China's corn yield potential, and their genetic contribution to Chinese corn has been increasing [5][6]. Using American maize germplasm is an effective way to improve the diversity of Chinese maize germplasm for identified and screened favorable allele donors due to its clear genealogical origin and abundant genetic variation [7]. Previous studies have shown that the growth period, the silking stage, the ear height, the plant height, and the kernel moisture concentration at the R6 stage could be used to determine a maize germplasm suitable for mechanical harvesting [8].…”
Section: Introductionmentioning
confidence: 99%
“…Cuban Flint is also called Cateto in Brazil, which combines well with Tuxpeño, but it is susceptible to viral diseases (Wang et al, 1998). Germplasms from CIMMYT include more than 200 populations, among them Pop33 which is a medium-maturity subtropical population improved by backcrossing from Pool 33 (Wang et al, 1998) and Pop45 which is a subtropical population that contains germplasm of BSSS (Iowa Stiff Stalk Synthetic), Tuxpeño, Cuban Flint, and Puerto Rico (Yong et al, 2013). Since 2000, many germplasms from CIMMYT have been introduced into China and intensively studied, which has helped broaden the Chinese maize germplasm base and improve grain yield (Chen et al, 2000a(Chen et al, , 2000bFan et al, 2005Fan et al, , 2008aFan et al, , 2008bFan et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis on Current Situation of Beijing E-Waste Recycling Network. As economically advanced city in China, Beijing's per capita amount of e-waste is much higher than the national average, and it has entered the peak of waste electrical and electronic products since 2003 [2]. Accompanied by the process of urbanization, sustainable growth of population size and upgrade of consumption structure, the amount of e-waste in Beijing increased rapidly.…”
Section: Analysis On Current Situation and Problems Of Beijing E-wast...mentioning
confidence: 99%